ANALISIS KONTRIBUSI KONSTELASI MULTI GNSS DALAM PENENTUAN POSISI MENGGUNAKAN METODE STATIK,RTK,DAN RTPPP PADA DAERAH TERTUTUP - Ali Fauzan, Syafiq
The extra-terrestrial method commonly used by land parcel surveyors is the static method and the Real-Time Kinematic (RTK) method that utilizes the Global Navigation Satellite System (GNSS) technology. Indonesia is located in the Asia Pacific region where the availability of GNSS satellites such as GPS, Glonass, Galileo, and Beidou strongly support the measurements. Measurements are usually done in a closed area with vegetation and building obstruction. The purpose of this study was to determine the data quality of static, RTK, and Real-Time Precise Point Positioning (RTPPP) measurement methods in closed areas and also to know the contribution of multi-satellite constellations for static, RTK, and RTPPP methods in closed areas. Data acquisition was carried out in various locations with high-density vegetation and building coverage in five baseline distances, i.e. 2.5 km, 5 km, 10 km, 20 km, and 50 km. Data quality assessment obtained from the value of Dilution Of Precision (DOP), multipath, Signal to Noise Ratio (SNR) and sky plot of observation data. The static method is processed with Leica Geo Office (LGO) software to determine the level of precision and accuracy of each combination of satellite constellations. Also for the data obtained using the RTK and RTPPP methods, the level of precision and accuracy will be analyzed. In closed areas, the use of multi-satellite constellations is the best solution to obtain data quality with an optimum level of accuracy and precision for both static and RTK methods. The use of GPS satellite constellation is not feasible because satellite geometry obtained in closed areas is insufficient. The RTPPP method cannot provide a good solution, all obtained data have a single solution.